Experiences, characteristics, and features of developing new towns between 1898 and 1970 - Mazdak Irani (European Journal of Geography)
The decision on developing a new town is always informed by the needs and requirements of regional and national planning on the basis of political viewpoints, natural recourses, industrial facilities, and population surplus viewpoints. In different areas, new towns were built to address the emerging social, economic, and environmental problems by supporting better living, enabling urban activities, and supporting industrial expansion. Following the review of the related literature, this study compared the theories and bases for building new towns and studied the experiences of different countries as examples. The present desktop research was carried out based on a narrative review in order to develop a framework for assessing the success of new town projects in response to the underlying needs and aims. Although the survey of literature did not result in harmonized measures of success or failure of new towns, the identified critical measures assist decision-and policy-makers to adopt appropriate strategies to assure a higher rate of success for developing new towns.